A Preliminary Approach to Ibn ’Arabi’s Theophanic Anthropology - Diyab, Adib Nayif (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Preliminary Approach to Ibn ’Arabi’s Theophanic Anthropology